1899 S.C. Acts 97, No. 67, § 1 - (:unkn) unknown (My University, 1899)
Be it enacted by the General Assembly of the State of South Carolina, That any person who shall engage in any boisterous conduct, under the influence of intoxicating liquors, or while feigning to be under the influence of such liquors, or without just cause or excuse, shall discharge any gun, pistol or other firearms while upon or within fifty yards of any public road, except upon his own premises, shall be guilty of a misdemeanor, and upon conviction thereof shall pay a fine of not more than one hundred dollars or be imprisoned for not more than thirty days.
Keywords: DISCHARGE